Strategic planning and decision-making for public and non-profit organizations - Valcik, Nicolas A. (Routledge, 2016)
This book provides administrators in public and non-profit organizations with direction and a framework from which to lead their organizations effectively. Taking a global approach to the issues administrators need to examine when managing a group of employees at any level (including budgeting and expenditures, forecasting, policy creation, and execution, communication, and reporting), this book explores the driving forces in organizational decision-making. Author Nick Valcik takes a holistic view on organizational management, beginning with the core aspects of public organizations and the leadership competencies necessary to manage an organization successfully. Designed to be used on undergraduate and graduate courses in public administration and in public affairs programs, the book discusses the basics of organizational structure, delves into risk management issues, and offers a set of tools that can be used by administrators to make informed decisions based on actual data or documented processes. Throughout the book, real world case studies provide students and practitioners with a clear understanding of how exactly the right decision tool may be applied when facing a particular decision in any organization.